Dekulturasi Budaya Yunani dalam Anthropodipus Adaptasi Oedipus di Colonus oleh Iswadi Pratama - Adhy Pratama Irianto (ESTETIK : Jurnal Bahasa Indonesia, 2024)
Iswadi Pratama, founder and artistic director of Teater Satu Lampung is an artist that focused to study two art disciplines at once, literature and theatre. His works are full of ideological criticism and responses to the political situation and the surrounding environment. In the show entitled Anthropodipus, Iswadi Pratama performs an intertextual interpretation and rewriting of the text Oedipus in Colonus by Sophocles with several anthropological approaches in artistic visualization, decoration, props, costumes, music, make-up, characterizations, and choreography. This paper aims to examine creativity and innovation based on Iswadi Pratama's artistic work with members of the Lampung Satu Theater in translating the Oedipus text in Colonus into Anthropodipus. The results of acculturation of various cultures in the creation of Anthropodipus' works resulted in the deculturation of Greek culture in the hypogram text. This makes the show held by Teater Satu Lampung unique and reflects Iswadi Pratama's artistic passion and innovation. The deculturation is intended to make works written before this Christian era closer to the audience in 2018 when this stage is being held. As a result, this stage received a positive response when it was staged in Lampung, Padang Panjang, and Jakarta from the number of viewers and the show's reviews from critics.